Arbovirus fevers in children and adults in the Astrakhan region: clinical cases - O. G. Kimirilova; G. A. Kharchenko (Детские инфекции (Москва))
Natural focal infections with transmissible transmission caused by viruses of West Nile Fever, Batai, Inco, Sindbis, Tyagin are registered in various territories of Russia, in the form of sporadic cases, characterized by polymorphism of clinical symptoms, from inapparent forms to severe, occurring with Central nervous system damage (meningitis, meningoencephalitis), which complicates the timely diagnosis and treatment of this pathology.Purpose: to describe our own clinical observations of five cases of arbovirus fevers.Results. Arbovirus fevers (West Nile Fever, Batai, Inko, Tyaginya) in the five clinical cases we have presented occurred in two clinical forms: catarrhal with hypertension syndrome, febrile fever and intense headache, vomiting in the absence of signs of inflammation in the CSF; and with damage to the central nervous system (meningitis). Catarrhal forms of arboviral fevers must be differentiated from ARVI, influenza, mononucleosis. Arbovirus fevers occurring with Central nervous system lesions (meningitis) had a significant similarity with enteroviral meningitis, both in terms of seasonality and clinical symptoms.Conclusion. In the territories of Russia endemic for mosquito fevers, in the summer period of the year, febrile patients with cerebral symptoms and / or meningeal symptoms should be examined for a group of arbovirus fevers.